Modeling and analyzing load profiles for fuel cell powered cargo bicycles - Daniel José Damas da Silva Leal (2019)
Proton exchange membrane fuel cells (PEMFCs) are the forefront for transportation applications because of the high efficiency and low pollutant emissions. The Polymer Fuel Cell Group of the German Aerospace Center (DLR) is rolling out a demonstration project for the use of electrical cargo bicycles powered by fuel cells, in urban delivery services. The performance and degradation expected from these fuel cells are yet to be known when they are subject to real operating conditions. The goal of this master thesis is to analyze different load cycles that simulate real driving profiles and study the performance and degradation of the cell along time. To study this, Ex-Situ and In-situ characterization of the cell will be made. In-situ techniques will be based on Cyclic Voltammetry (CV) and Electrochemical Impedance spectroscopy (EIS). To evaluate the changes on the surface of different parts of the cell and assess its degradation, Ex-Situ analysis will be performed using scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). Additionally a data acquisition unit will be developed to gather real-time information of the testing station.